MEASUREMENT ANALYSIS ON THE LEVEL OF COOPERATIVE PERFOMANCE BASED ON THE BALANCE SCORECARD METHOD APPROACH: Case Study of The Bahrul Ulum Islamic Boarding School Cooperative Subang District - putri ayu; Eviana Putri; Icih Icih (JABI (Journal of Accounting and Business Issues), 2022)
The purpose of this study was to determine how the level of cooperative performance through the Balanced Scorecard method approach which was reviewed through four perspectives, namely (1) financial perspective, (2) customer service perspective, (3) internal business perspective, and (4) growth and development perspective. learning. Based on these objectives, this research uses a quantitative descriptive method with a case study approach. Where the object in the research is the Bahrul Ulum Islamic Boarding School Cooperative. The type of data used in this study is secondary data, namely data taken from the 2020-2021 RAT report. The data collection technique is through library research and documentation. And the data analysis technique in this study consisted of 11 measurement indicators. The results of this study indicate that the performance of the Bahrul Ulum Islamic Boarding School Cooperative in 2021 as a whole gets a score of 50.00 out of a total weight of 100, meaning that the cooperative has not reached the target, with details as follows: (1) the financial perspective has not reached the target with a score of only 28.00, (2) the customer perspective has not reached the target with a score of only 4.00, (3) the internal business perspective has reached the target with a score of 10.00, (4) the growth and learning perspective has reached the target with a score of 10.00. From this analysis, the Bahrul Ulum Islamic Boarding School Cooperative has not fully achieved the target, this is because the Bahrul Ulum Islamic Boarding School Cooperative has not paid close attention to the performance that has been achieved, especially in terms of finances and customers, which is marked by a decrease in SHU in 2021, which is 15% when compared to SHU in 2020.